ESTABLISHING RELIGIOUS CHARACTER THROUGH SCOUTING EXTRACURRICULAR ACTIVITIES AMONG STUDENTS AT BONE ISLAMIC SENIOR SCHOOL - Rabiatul Adawiyah; Wahyuddin N; Usman Usman (Universitas Islam Negeri Alauddin Makassar, 2021)
This article discusses the formation of the religious character of students through scout extracurricular activities where 1 Bone The type of research used by the author is qualitative research (Field Research). Qualitative research is descriptive, namely a form of research aimed at describing an object, existing phenomena which will then be outlined in a narrative writing. The key instrument is the researcher himself, namely the researcher as a planner, implementer in collecting data, analyzing, interpreting data, and reporting on the results of his research. In order to facilitate students so that their character can develop, the school forms many extracurricular activities to support the learning process.